Airline passengers' perceptions of service quality: themes in online reviews. Issue 2 (13th February 2019) - Brochado, Ana; Rita, Paulo; Oliveira, Cristina; Oliveira, Fernando
Abstract : Purpose: This paper aims to identify the main themes shared in online reviews by airline travellers, as well as which of these themes were linked with higher and lower value for money ratings. Design/methodology/approach: The research used mixed content analyses (i.e. quantitative and qualitative) to examine 1, 200 reviews of six airline companies shared by airline travellers in a social media platform. Findings: The analyses revealed nine themes in descriptions of airline travel experiences. These are the core services during "flights", "airport" operations, crew and ground "staff", ticket "classes", "seats", inflight "services", "entertainment", overall experiences of "airlines" and post-purchase recommendations of with which companies to "fly". Low value for money ratings are linked with the "airport" and "flights" themes. Originality/value: The results offer useful insights into airline travellers' overall experiences based on social media information and facilitate the identification of the main themes linked with different value for money ratings.